Bibliometric Analysis of Firm Adaptation Strategies in a Hypercompetitive Environment - Loso Judijanto; Muhamad Ammar Muhtadi (Westscience Press, 2024)
This study utilizes bibliometric analysis to map the scholarly landscape of research in hypercompetitive environments and strategic management. Through VOSviewer visualizations, we identified thematic clusters, examined trends over time, analyzed under-researched opportunities, and explored patterns of author collaboration. Our findings reveal a significant shift from foundational theoretical research towards more practical, industry-specific strategies that address dynamic competitive challenges. We identified key thematic areas such as industry dynamics, leadership in hypercompetition, globalization impacts, and sector-specific adaptation strategies. Furthermore, less-explored areas such as opportunity recognition and competitive dynamics offer fruitful avenues for future research. The author collaboration network analysis highlighted both active clusters and potential areas for increased interdisciplinary collaboration, suggesting a maturing yet still siloed research community. This comprehensive overview not only synthesizes existing research but also highlights strategic gaps and opportunities for future scholarly work in the domain of strategic management within hypercompetitive contexts.